2020
DOI: 10.1111/jfs.12852
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Salmonella serotypes S. Enteritidis and S. Typhimurium in poultry and poultry products

Abstract: Salmonella continues to be a major food safety and public health threat. In the present study, Salmonella enterica subsp. enterica serotypes Enteritidis (SE) and Typhimurium (ST) were isolated from poultry and characterized for virulence, antimicrobial susceptibility, and biofilm formation. Prevalence of Salmonella serotypes in poultry was 3.35%; predominant serotypes isolated were S. Enteritidis (68.1%) and S. Typhimurium (31.8%). Source-wise, Salmonella were isolated from retail market chicken meat (4.8%), l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 75 publications
1
14
2
Order By: Relevance
“…Other genes present on the Salmonella chromosomes found in this study were stn and fliC, which play a role in enterotoxin production and encode phase-1 flagellin, respectively [26]. All Salmonella isolates contained the stn gene, which has also been reported in all poultry isolates from studies conducted in China, Benin, and India [72][73][74]. However, the fliC gene in our study was only detected in the wastewater isolates obtained during the house decontamination.…”
Section: Virulencesupporting
confidence: 60%
“…Other genes present on the Salmonella chromosomes found in this study were stn and fliC, which play a role in enterotoxin production and encode phase-1 flagellin, respectively [26]. All Salmonella isolates contained the stn gene, which has also been reported in all poultry isolates from studies conducted in China, Benin, and India [72][73][74]. However, the fliC gene in our study was only detected in the wastewater isolates obtained during the house decontamination.…”
Section: Virulencesupporting
confidence: 60%
“…The antigenic characteristics of the isolated Salmonella strains showed that S. Enteritidis (80.4%) was the predominant serotype. Consistently, in China [12], S. Enteritidis was the predominant serotype (40.3%) isolated from chicken carcasses; in Iran [57], S. Enteritidis was the predominant serotype in 43% of cases of contamination of poultry carcasses; and in India [58], S. Enteritidis was the predominant serotype (68.1%) in poultry products. The percentage of the prevalence of S. Enteritidis in this study was higher than similar data obtained from Saudi Arabia (40%) [59] and Pakistan (9%) [60].…”
Section: Discussionmentioning
confidence: 86%
“…Salmonella serovars have been shown to infect various domesticated animals, including cattle, poultry, pigs, and sheep. Infected animals may exhibit symptoms ranging from mild gastroenteritis to death in extreme cases of Salmonella infection [ 6 ]. Most cases of salmonellosis are attributed to eggs and chicken meat consumption.…”
Section: Introductionmentioning
confidence: 99%